Marriage and the mystery of the Gospel - Ortlund, Raymond C. (U.S.A, 2016)
Marriage is so much more than a human institution. The Bible teaches that marriage was created by God and reveals an eternal mystery -- the mystery of the gospel. In this way, marriage paints a picture of our salvation in and through Jesus Christ. Pastor Ray Ortlund traces the Bible's teaching on marriage from Genesis to Revelation -- revealing how marriage stands at the center of God's redemptive purposes for the world. Helping us grasp a cosmic vision of this oft-misunderstood institution, this volume honors and exalts marriage as a grand display of the gospel, offering guidance and hope for our own marriages today.
Keywords: Marriage -- Religious aspects -- Christianity